مظاهر اللهجات العربية - Dian Ekawati (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Language is one of the means to convey the thought and opinions of one person to another in the form of sentence. There are many varieties and difference of Arabic. In the world, due to the differences of: geography, voice, social habits, environment, and various traditions, dialect is a collection of properties of language that emerges from the special circumstances of individual users of language as means of communication among them.The relationship between language and dialect is the relationship of general and specific in terms of language.Dialect has three kinds of properties, that is: connecting the sound, connection word, and connection the sentence structure.The benefit of dialect difference in Arabic is the attitude of knowing each other among the Arabic users.